Verso una democrazia multiplebiscitaria? - Antonelli, Francesco (SocietàMutamentoPolitica, 2011)
The aim of this paper is to analyze the transformation of populism and charismatic phenomena in contemporary societies and, in particular, in Italian society. The argument is that these transformations, are the effects of diffusion of new technologies and structural changes in the functioning of social systems, involving a growing fragmentation of democracy. Instead of the traditional charismatic leader described by Weber, we face a number of leaders who are directly appeal to the people, through the mainstream media or new media, such as normal and not exceptional for political action. The first three paragraphs of the essay are devoted to general analysis of these transformations in the context of liquid modernity. In the last paragraph, we will instead develop some considerations and reflections about the Italian case.